Purinergic signaling mediated by P2X7 receptors controls myelination in sciatic nerves. Issue 10 (5th June 2014) - Faroni, A.; Smith, R.J.P.; Procacci, P.; Castelnovo, L.F.; Puccianti, E.; Reid, A.J.; Magnaghi, V.; Verkhratsky, A.
<x xml:space="preserve">Abstract</x> Adenosine‐5′‐triphosphate, the physiological ligand of P2X receptors, is an important factor in peripheral nerve development. P2X7 receptor is expressed in Schwann cells (SCs), but the specific effects of P2X7 purinergic signaling on peripheral nerve development, myelination, and function are largely unknown. In this study, sciatic nerves from P2X7 knockout mice were analyzed for altered expression of myelin‐associated proteins and for alterations in nerve morphology. Immunohistochemical analyses revealed that, in the wild‐type peripheral nerves, the P2X7 receptor was localized mainly in myelinating SCs, with only a few immunopositive nonmyelinating SCs. Complete absence of P2X7 receptor protein was confirmed in the sciatic nerves of the knockout mice by Western blot and immunohistochemistry. Western blot analysis revealed that expression levels of the myelin proteins protein zero and myelin‐associated glycoprotein are reduced in P2X7 knockout nerves. In accordance with the molecular results, transmission electron microscopy analyses revealed that P2X7 knockout nerves possess significantly more unmyelinated axons, contained in a higher number of Remak bundles. The myelinating/nonmyelinating SC ratio was also decreased in knockout mice, and we found a significantly increased number of irregular fibers compared with control nerves. Nevertheless, the myelin thickness in the knockout was unaltered, suggesting a stronger role for P2X7 in determining SC maturation than in myelin formation. In conclusion, we present morphological and molecular evidence of the importance of P2X7 signaling in peripheral nerve maturation and in determining SC commitment to a myelinating phenotype. © 2014 Wiley Periodicals, Inc.